2021
DOI: 10.1002/maco.202012133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti addition on microstructure and the associated corrosion behavior of a 22Cr‐5Ni duplex stainless steel

Abstract: The effects of Ti addition on microstructure and the associated electrochemical properties of 22Cr-5Ni duplex stainless steel were evaluated using X-ray diffraction, X-ray electron probe microanalysis, electron backscattered diffraction, scanning Kelvin probe force microscopy, scanning electron microscopy-energy-dispersive X-ray spectroscopy, electrochemical techniques, and X-ray photoelectron spectroscopy. The results indicated that the addition of a minor amount of Ti refined the grains, improved the pitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, the pitting potential slightly increased when adding 8.03 wt.% in the solid solution state to duplex stainless steel [63] . Feng et al reported that manganese is detrimental when aging at 800 °C for forming precipitants [64] . Therefore, it can be concluded that manganese increases the number of pit nucleation sites when it exists in the form of precipitants (inclusions or secondary phases).…”
Section: Manganese Elementmentioning
confidence: 99%
“…However, the pitting potential slightly increased when adding 8.03 wt.% in the solid solution state to duplex stainless steel [63] . Feng et al reported that manganese is detrimental when aging at 800 °C for forming precipitants [64] . Therefore, it can be concluded that manganese increases the number of pit nucleation sites when it exists in the form of precipitants (inclusions or secondary phases).…”
Section: Manganese Elementmentioning
confidence: 99%